White‐beam X‐ray radioscopy and tomography with simultaneous diffraction at the EDDI beamline. (24th July 2013) - García‐Moreno, F.; Jiménez, C.; Kamm, P. H.; Klaus, M.; Wagener, G.; Banhart, J.; Genzel, Ch.
<x xml:space="preserve">Abstract</x> A set‐up for simultaneous imaging and diffraction that yields radiograms with up to 200 frames per second and 5.6 µm effective pixel size is presented. Tomograms and diffractograms are acquired together in 10 s. Two examples illustrate the attractiveness of combining these methods at the EDDI beamline for in situ studies.